INS-1 베타 세포에서 Exendin-4에 의한 Cyclin D1 발현에 관여하는 cAMP/PKA의 작용 - 류경렬; Gyeong Ryul Ryu; 강정훈; Jung Hoon Kang; 장화인; Hwa In Jang; 고승현; Seung Hyun Ko; 정인경; In Kyung Jeong; 이덕주; Duck Joo Rhie; et al. (Diabetes & metabolism journal, 2005)
연구배경: 글루카곤양 펩티드-1 수용체 자극제 (GLP-1 receptor agonist)인 exendin-4 (EX-4)는 췌도 베타세포의 증식을 촉진하는 것으로 보고되었다. 따라서 EX-4가 세포 주기 중 G1 주기에서 S 주기로의 진입을 유도하는 cyclin D1의 발현에 미치는 영향과 이에 관여하는 기전을 베타 세포주인 INS-1 세포에서 관찰하였다. 방법: INS-1 세포에 EX-4를 처리 후 cyclin D1 단백질의 발현을 Western blot으로 관찰하였고, cyclin D1의 발현에 MAPKs가 관여하는 지를 각각의 억제제를 전처리하여 관찰하였으며, ERK1 과발현 vector를 transfection한 후 cyclin D1 단백질의 발현을 조사하였다. 또한 세포내의 cAMP를 증가시키는 forskolin (10 M)과 PKA 억제제인 H-89를 처리하였을 때 cyclin D1 단백질의 발현을 조사하였다. 결과: EX-4는 농도 의존적으로 cyclin D1 단백질의 발현을 증가시켰으며, EX-4는 MAPKs 중에서 ERK1/2의 인산화를 증가시켰지만 ERK의 상위 단계인 MEK 억제제 PD 98059를 전처리하였을 때 cyclin D1 단백질의 발현에는 변화가 없었다. 또한 ERK1을 과발현시에도 cyclin D1 단백질의 발현에는 변화가 없었다. 그러나 forskolin을 처리하였을 때 cyclin D1 단백질은 크게 증가하였으며, H-89를 전처리 시에 EX-4에 의한 cyclin D1 단백질의 증가는 억제되었다. 결론: EX-4는 INS-1 세포에서 cyclin D1의 발현을 증가시키며, 이 때 MAPKs는 관여하지 않으며, EX-4가 활성화시킨 cAMP/PKA 경로를 통하여 cyclin D1의 발현을 증가시킨다고 생각된다. -Background: Glucagon-like peptide-1 (GLP-1) and exendin-4 (EX-4) have been known to induce pancreatic islet proliferation and increases in the -cell mass. Cyclin D1 is a key protein responsible for the entry of the G into the S phase, thereby contributing to cell proliferation. Therefore, the effect of EX-4 on the expression of cyclin D1 in INS-1 cells, a rat pancreatic -cell line, was investigated. The involvement of either mitogen-activated protein kinases (MAPKs) or cyclic adenosine 5'-monophosphate/protein kinase A (cAMP/ PKA) in the EX-4-induced cyclin D1 expression was also examined. Methods: INS-1 cells were treated with EX-4 (10 nM), and the cyclin D1 protein levels then determined by Western blot. To investigate the involvement of MAPKs in the EX-4- induced cyclin D1 expression, either a combined treatment of MAPKs inhibitors or transient transfection of extracellular signal-regulated kinase-1 (ERK1) was performed. The effect of cAMP on the EX-4-induced cyclin D1 expression was also examined by treatments with forskolin, an adenylyl cyclase activator, and H-89, a PKA inhibitor. Results: EX-4 increased the expression of cyclin D1 protein in a dose-dependent manner. Although EX-4 induced phosphorylation of ERK1/2, the treatment with PD 98059 or the overexpression of ERK1 had no effect on the EX-4-induced cyclin D1 expression. However, forskolin significantly induced the expression of cyclin D1, whereas the pretreatment of H-89 inhibited the EX-4-induced cyclin D1 expression.Conclusion: These results suggest that EX-4 induce cyclin D1 expression in INS-1 cells via cAMP/PKA pathway, but this is not due to ERK activation KCI Citation Count: 0